Sistem Monitor Kelembaban Tanah Berbasis Internet of Things (IoT) - Julianto Wira Mansa; Quido Conferti Kainde; Ferdinan Ivan Sangkop (JOINTER : Journal of Informatics Engineering, 2022)
Abstract— Abstract- Soil moisture is a water content that partially or completely washes the soil pores. So far, the process of checking soil moisture is still done manually, where farmers have to come to the field directly. To assist the process of checking the soil, the researchers designed and built a soil moisture monitoring system based on the Internet of Things which aims to simplify the process of monitoring soil moisture without having to come to the field. In implementing the development of this monitoring system, the author uses the prototype system development method. This system implements an Arduino UNO microcontroller, ESP8266-01 WiFi transmitter, YL-69 soil moisture sensor, and LCD as part of the monitor system. Based on the results of the design and testing of this soil moisture monitoring system, it allows users to get information on the state of soil moisture levels without being limited by distance by using the internet network where Thingspeak and ThingView work as a monitoring media where this system is useful for helping farmers to know the level of soil moisture through smartphones and PC.